SOME ISSUES OF IMPROVING THE LEGISLATION - Исмагулов, Кайрат Еслямкалиевич; Turetskiy , Николай Николаевич (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2023)
Service in special state bodies is a special type of public service in positions in national security bodies, an authorized body in the field of foreign intelligence, in the Security Service of the President of the Republic of Kazakhstan. Independent (departmental) laws regulate each of these three areas of activity. In particular, in the field of national security, the Law «On the National Security Bodies of the Republic of Kazakhstan» is in force, in the field of foreign intelligence - the Law «On Foreign Intelligence», in the third area - the Law «On the State Security Service of the Republic of Kazakhstan». The object of research and analysis of effectiveness was the Law of the Republic of Kazakhstan «On special state bodies of the Republic of Kazakhstan», as it covers all employees of the above bodies. The adoption of this Law marked a new stage in the legal regulation of the institution of public service in special state bodies, since earlier public-service relations in the system of special state bodies were regulated by various legal acts. The new model of state special bodies has made it possible to improve the quality of personnel and the effectiveness of national special services, to significantly improve the organization and functioning of the institute of special public service. The authors in the article considered the legal status of employees of special state bodies, carried out a comparative analysis with the regulatory framework for the activities of similar services in foreign countries, provided statistical data on the number of legislative changes, identified some outdated norms, minor contradictions and shortcomings that do not negatively affect the work of special state bodies developed proposals for their elimination.